Hidropolítica e conflitos por água: disputas territoriais e acesso à água no município de Dona Inês (PB) - Silva, Aryan Carlos de Oliveira (2023)
Access to water is currently a cause of an increasing number of conflicts, especially in semiarid regions that lack abundant water reserves. In the municipality of Dona Inês, in the state of Paraíba, Brazil, located in a semi-arid scenario, water conflicts take on various forms due to the annual water scarcity, exacerbated by the lack/inefficiency in water resource management by the government. This study is based on the hypotheses that these conflicts occur a) due to the demand for different water uses and the condition of access to water by users; b) because of water scarcity and attempts at monopolizing water resources by certain landowners; c) due to a mercantilist view of water and the difficulty in implementing universal policies that promote community access to water resources. The overall objective of this master's research is to analyze the factors responsible for water conflicts in the Dona Inês Mountain Range Sub-basin, within the context of territorial disputes in the municipality of Dona Inês, Paraíba. The specific objectives are as follows: a) Identify the causes of the origin of water conflicts in the study area; b) Analyze how different actors have access to local water resources; c) Assess water resource public policies impacting the study area; d) Analyze the relationship between land structure and water conflicts. The methodological procedures were operationalized as follows: a) Literature review; b) Compilation of Decrees/Laws; c) Production of digital/cartographic and statistical information; d) Fieldwork in the municipality of Dona Inês. To analyze water conflicts, a temporal focus from the years 2000 to 2020 is proposed. Therefore, various water conflicts have been identified and mapped in the study area. We have found that microscales and social daily life, mediated by power relations, form a scenario for the outbreak of water conflicts within a hydropolitical context. The different actors - particularly the government and landowners/users - at different scales, interrelate and establish various typologies of water conflicts.